Analysis of e-learning readiness level implementation in islamic senior high school south jakarta, indonesia: Review in biological learning - Muhammad Hisan Alfani Muslim; Zulfiani Zulfiani (Biosfer, 2023)
The utilization of E-Learning as one of the innovations in learning provides a richer and more flexible digital learning experience, where learning can be done anytime and anywhere without being limited by space or time. Its use requires good physical and mental readiness so that e-learning can run optimally. This study aims to determine the level of readiness for the implementation of e-learning in Islamic Senior High School South Jakarta, Indonesia. A survey method was used in this study, survey data were collected through a questionnaire adapted from the Aydin & Tasci ELR model which uses four factors of readiness namely human, self-development, technology, and innovation. The four factors are constructed from resources, skills, and attitudes. The sample in this research is Islamic Senior High School in South Jakarta, Indonesia. The results showed that Islamic Senior High School in South Jakarta was categorized as ready and could be continued in implementing e-learning (Mtotal=4.24 > 4.21). There are two factors that are categorized as ready and can be continued, namely technology and innovation factors, the other two factors, namely human beings and self-development are categorized as ready but need a little improvement. The resource aspect is the main focus in human factors, self-development, and innovation that requires a little improvement. These factors can be the focus of attention. They can be used as a reference for Islamic Senior High School A in South Jakarta in making improvements and improvements in the implementation and utilization of e-learning.